Role of a BRCT domain in the interaction of DNA ligase III-alpha with the DNA repair protein XRCC1. - Taylor, R; Wickstead, B; Cronin, S; Caldecott, K (1998)
The BRCT domain (for BRCA1 carboxyl terminus) is a protein motif of unknown function, comprising approximately 100 amino acids in five conserved blocks denoted A-E. BRCT domains are present in the tumour suppressor protein BRCA1 [1-3], and the domain is found in over 40 other proteins, defining a superfamily that includes DNA ligase III-alpha and the essential human DNA repair protein XRCC1. DNA ligase III-alpha and XRCC1 interact via their carboxyl termini, close to or within regions that contain a BRCT domain [4]. To examine whether the primary role of the carboxy-terminal BRCT domain of XRCC1 (denoted BRCT II) is to mediate the interaction with DNA ligase III-alpha, we identified the regions of the domain that are required and sufficient for the interaction. An XRCC1 protein in which the conserved D-block tryptophan was disrupted by point mutation retained the ability to interact with DNA ligase III-alpha, so this tryptophan must mediate a different, although conserved, role. XRCC1 in which the weakly conserved C-block was mutated lost the ability to interact with DNA ligase III-alpha. Moreover, 20 amino acids spanning the C-block of BRCT II conferred full DNA ligase III-alpha binding activity upon an unrelated polypeptide. An XRCC1 protein in which this 20mer was deleted could not maintain normal levels of DNA ligase III-alpha in transfected rodent cells, a phenotype associated with defective repair [5]. In summary, these data demonstrate that a BRCT domain can mediate a biologically important protein-protein interaction, and support the existence of additional roles.